Detections of [O iii] 88 μm in two quasars in the reionization epoch. (17th September 2019) - Hashimoto, Takuya; Inoue, Akio K; Tamura, Yoichi; Matsuo, Hiroshi; Mawatari, Ken; Yamaguchi, Yuki
ABSTRACT: We report on detections with the Atacama Large Millimeter/sub-millimeter Array of the far-infrared [O iii ] 88 μm line and the underlying dust continuum in two quasars in the reionization epoch, J205406.48−000514.8 (hereafter J2054−0005) at z = 6.0391 ± 0.0002 and J231038.88+185519.7 (hereafter J2310+1855) at z = 6.0035 ± 0.0007. The [O iii ] luminosities of J2054−0005 and J2310+1855 are L [O iii] = (6.8 ± 0.6) × 10 9 and (2.4 ± 0.6) × 10^9 L ⊙, corresponding to ∼0.05% and 0.01% of the total infrared luminosity, L TIR, respectively. Combining these [O iii ] luminosities with [C ii ] 158 μm luminosities in the literature, we find that J2054−0005 and J2310+1855 have [O iii ]-to-[C ii ] luminosity ratios of 2.1 ± 0.4 and 0.3 ± 0.1, respectively, the latter of which is the lowest among objects so far reported at z > 6. Combining [O iii ] observations at z ≈ 6–9 from our study and the literature, we identify the [O iii ] line deficit: objects with a larger L TIR (total infrared luminosity) have lower L [O iii] -to- L TIR ratios. Furthermore, we also find that the anti-correlation is shifted toward a higher L TIR value when compared with the local [O iii ] line deficit.